Knowledge Map of Gender Equality in Cross-generational Awareness for Education: A Bibliometric Approach - Ibrahim, Intan Maharani; Suryadi, Karim; Darmawan, Cecep; Nurbayani, Siti (KnE Social Sciences, 2024)
The issue of gender in global cross-generational consciousness must be urgently addressed. Gender equality (Sustainable Development Goal 5 or SDG5) should be the responsibility of all countries around the world. As a result, this study intends to draw a map of knowledge on gender issues in consciousness across generations to investigate the state of research and future possibilities. This study aims to build a knowledge map that provides a comprehensive understanding of gender issues in awareness across generations. Vosviewer was used to perform bibliometric techniques on 370 English articles from Scopus on cross-generational awareness and gender equality themes. The study emphasizes the continued focus and upward trend of publications after cluster analysis and time series analysis and outlines the important authors, and research countries on the issue. The US has made significant contributions and influenced the UK and Australia. Gender, generation, gender equality, awareness, generational differences, gender issues, culture, education, gender inequality, feminism, health equity, diversity, social psychology, policy, and sustainable development are some of the groups of terms generated by the author’s collaboration. As a result, the conclusions propose that research on gender issues could be expanded to include more authors, fields, subjects, and other diverse cooperative sectors. The implications of this knowledge mapping go beyond academia, holding practical and policy relevance, especially regarding gender equality and cross-generational awareness. This study is critical to inform future policies and practices aimed at fostering inclusivity and equality across generations. Keywords: bibliometric analysis, cross-generational awareness, education, gender equality